MODERN DENTAL ALLOYS: STATUS OF THE ISSUE - V.D. Kindii (Український стоматологічний альманах)
Modern dentistry offers a wide range of materials for restoration of lost teeth and aesthetic restoration. Dental alloys occupy a special place among them. Their properties directly affect the durability, aesthetics and biocompatibility of dental structures.